2014
DOI: 10.3389/fnbeh.2014.00056
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent effects of an early life treatment in rats that increases maternal care: vulnerability or resilience?

Abstract: Early life stress (ELS) in rodents has profound long-term effects that are partially mediated by changes in maternal care. ELS not only induces “detrimental” effects in adulthood, increasing psychopathology, but also promotes resilience to further stressors. In Long-Evans rats, we evaluated a combination of two procedures as a model of ELS: restriction of bedding during the first post-natal days and exposure to a “substitute” mother. The maternal care of biological and “substitute” mothers was measured. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 150 publications
7
36
0
Order By: Relevance
“…Our data are in line with previous studies from our lab (Fuentes et al, 2014;Peña et al, 2009) and with most previous reports measuring basal plasma corticosterone (e.g. Patchev et al, 1999;Rhodes et al, 2002;Seale et al, 2004a).…”
Section: Endocrine Responsesupporting
confidence: 83%
“…Our data are in line with previous studies from our lab (Fuentes et al, 2014;Peña et al, 2009) and with most previous reports measuring basal plasma corticosterone (e.g. Patchev et al, 1999;Rhodes et al, 2002;Seale et al, 2004a).…”
Section: Endocrine Responsesupporting
confidence: 83%
“…However, increased maternal care failed to recover MSEW-related impairment of neurobiological functions and behaviours during adolescence, like locomotion deficits, responses to stress and the manifestation of anhedonia related to a lack of preference for saccharine. We found that several of these alterations were more striking in females, reflecting their greater vulnerability to stress, as previous reported (Becker et al, 2007;Fuentes et al, 2014).…”
Section: Discussionsupporting
confidence: 54%
“…Experimental and clinical studies have shown that the immaturity and plasticity of the central nervous system during childhood make it particularly sensitive to stress at a young age, which may cause significant changes in brain structure and function (Lupien et al, 2009). In recent years, various rodent behavioural models of early life stress, such as maternal separation, have been used to study the neurobiological basis of emotional and motivational disorders (Fuentes et al, 2014;Martini and Valverde, 2012;Pryce et al, 2001aPryce et al, , 2001b. Maternal separation with early weaning (MSEW) (George et al, 2010) attempts to reduce any potential compensatory maternal care after maternal deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond appearances, however, there are reasons to believe that the signaling effect captures a psychologically meaningful aspect embedded in the traditional gambling environment. First, the neurological basis for gambling disorders may be based in reward anticipation (e.g., Linnet, 2014) and the signaled-delay procedure accentuates that aspect of the risky choice contingency. Second, this task has shown promise as a means to predict individuals with a gambling habit.…”
Section: Discussionmentioning
confidence: 99%